Awig-Awig Management of Marine and Fisheries Resources West Lombok - Yulianingsih, Wiwin; Simangunsong, Frans; Arief Syahroni, Muh. (CV. Inara, 2022)
Awig-awig as the foundation of local wisdom, including in the management of marine and fisheries resources in West Lombok. The awig-awig arrangements include the prohibition of bombing and potassium, zoning of fishing groups, pumice waste, and the collection of marine coral. Awig-awig is written as a guideline in fisheries management as a form of sustainable coastal community development. Awig-Awig as a form of collective awareness of the community whose obedience is very large which has adapted to the conditions of the local community.